Hybrid control and motion planning of dynamical legged locomotion - Sadati, Nasser; Wiley eBooks (Hoboken, N.J. : Wiley, 2012)
"This book provides a comprehensive presentation of issues and challenges faced by researchers and practicing engineers in motion planning and hybrid control of dynamical legged locomotion. The major features range from offline and online motion planning algorithms to generate desired feasible periodic walking and running motions and tow-level control schemes, including within-stride feedback laws, continuous time update laws and event-based update laws, to asymptotically stabilize the generated desired periodic orbits. This book describes the current state of the art and future directions across all domains of dynamical legged locomotion so that readers can extend proposed motion planning algorithms and control methodologies to other types of planar and 3D legged robots"--
"This book provides a comprehensive presentation of issues and challenges faced by researchers and practicing engineers in motion planning and hybrid control of dynamical legged locomotion"--
Preliminaries in Hybrid Systems -- Asymptotic Stabilization of Periodic Orbits for Walking with Double Support Phase -- Asymptotic Stabilization of Periodic Orbits for Planar Monopedal Running -- Online Generation of Joint Motions During Flight Phases of Planar Running -- Stabilization of Periodic Orbits for 3D Monopedal Running -- Stabilization of Periodic Orbits for Walking with Passive Knees -- Continuous-Time Update Laws During Continuous Phases of Locomotion. -- Index.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Mobile robots; Robots -- Motion; Walking; TECHNOLOGY & ENGINEERING -- Robotics; TECHNOLOGY & ENGINEERING -- Automation; Mobile robots; Robots -- Motion; Walking; Electronic books